Researching Dreams The Fundamentals - Schredl, Michael (Cham : Springer International Publishing, 2018)
What can be gleaned from the study of our dreams? The book not only presents a comprehensive introduction to the research obtained so far but also provides the tools to carry our scientific dream studies-including the shortcomings and strengths of various approaches. Topics include the factors of dream recall; the continuity hypothesis of dreaming; the relationship between physiology and dream content; etiology and therapy of nightmares; and lucid dreaming.
1. Definitions -- 2. Dream Recall -- 3. Dream Content Analysis -- 4. Dream Behavior and Dream Content in Healthy Persons. - 5. Dream Content and Physiology -- 6. Dreams and Mental Disorders -- 7. Nightmares -- 8. Lucid Dreaming -- 9. Functions of Dreaming.
Behavioral Science and Psychology
text file PDF
Keywords: Psychology